"The effect of using Quasnir’s segments in teaching mathematics on the achievement of fourth-grade students primary school" - Halah Adnan Kadhim ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The aim of the current research is to identify the effect of using Quasnir’s segments in teaching mathematics on the achievement of female students Fourth grade of primary school, and to achieve the goal of the research, the researcher formulated the hypothesis: There is no statistically significant difference at the level of significance (0.05) between the average achievement scores of the experimental group students (who study mathematics using Quasner’s cut-offs) and the average achievement scores of the control group students (who study the same subject in the same way). The current research was limited to fourth grade students in one of the schools in Maysan Governorate for the academic year (2018/2019) , the researcher relied on the experimental design with two groups, experimental and the second control, and the number of sample members was (70) female students. By (35) female students for the experimental group and(35)female students for the control group. The two research groups were rewarded in several variables (pre-knowledge test in mathematics, chronological age calculated by month, previous achievement in mathematics. An achievement test of (20) items was prepared and the validity of the content was verified, and the Kewder-Richardon equation was used to calculate the stability of the achievement test and its value was (0.85) , and the (t-test) was used) for two independent samples for data processing, and the researcher found a statistically significant difference at the significance level (0.05) between the mean scores of the experimental and control group and in favor of the experimental group in the achievement test, and accordingly the researcher made some recommendations and suggestions .